2021
DOI: 10.1021/acsapm.1c00506
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Polymer Containing Menthoxy Triazine

Abstract: An antifungal polymer containing menthoxy triazine was synthesized by a polycondensation of 2,4-dichloro-6-menthoxy-1,3,5-triazine (DMT) with 4,4-oxidianiline (ODA) and named as P­(MT-alt-ODA). To emphasize the antifungal performance of the menthoxy group, series of similar triazine polymers derived correspondingly with hydrogen, ethoxy, and decoxy groups were prepared and served as controls. The spores of Aspergillus niger were used for an antifungal evaluation. Only P­(MT-alt-ODA) can effectively inhibit the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Menthol is a typical terpenoid molecule whose modified materials have emerged as candidates for antimicrobial adhesion. 34,35 Compared with borneol, menthol is more likely to produce various derivatives due to its low spatial resistance and high reactivity. 36,37 Therefore, skeleton modification of PET with the menthol moiety should be an appropriate method to impart antimicrobial adhesion properties to PET.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Menthol is a typical terpenoid molecule whose modified materials have emerged as candidates for antimicrobial adhesion. 34,35 Compared with borneol, menthol is more likely to produce various derivatives due to its low spatial resistance and high reactivity. 36,37 Therefore, skeleton modification of PET with the menthol moiety should be an appropriate method to impart antimicrobial adhesion properties to PET.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, stereochemical strategies have received special attention because of their safe, nontoxic, nonrelease, and long-term advantages. The theoretical basis of this antibacterial strategy is the selective recognition by microorganisms of chiral terpenoid molecules (borneol or menthol). The chiral terpenoid molecule-grafted surfaces and polymers exhibited excellent antimicrobial (bacterial and fungal) properties. The related studies have shown that the antimicrobial adhesion performance based on stereochemistry is closely related to the number of grafted chiral molecules, , indicating that the increase of the modification density of stereochemical terpene molecules will help to improve the antimicrobial adhesion properties of modified PET. Menthol is a typical terpenoid molecule whose modified materials have emerged as candidates for antimicrobial adhesion. , Compared with borneol, menthol is more likely to produce various derivatives due to its low spatial resistance and high reactivity. , Therefore, skeleton modification of PET with the menthol moiety should be an appropriate method to impart antimicrobial adhesion properties to PET. Triazine has been used as a suitable carrier for polymer synthesis because it can be replaced by different amine nucleophiles to produce triazine derivatives with different numbers of substitutions, depending on the reaction temperature .…”
Section: Introductionmentioning
confidence: 99%
“…An interesting concept involves capturing and quarantining the fungi, which isolates them from the internal environment instead of killing them. Li et al created a "spore prison" with menthol modified 2,4,6-Trichloro-1,3,5-triazine that firmly confined the fungi in menthoxy units for suppression of spore spread and germination (Li et al, 2021b). The spore prison potentially avoids the development of fungal fragment-induced pro-inflammatory responses (Oya et al, 2019).…”
Section: Antifungal Medical Devicesmentioning
confidence: 99%
“…34,35 Li et al successfully synthesized polyamides containing a triazine structure and exhibited good inhibition of fungal spores. 36 Therefore, it is promising that antimicrobial PET can be prepared by using menthoxytriazine derivatives as diacid units.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the insertion of menthol molecules into the polymer may be a good way to solve this problem. Triazine is a low-cost commercial available compound that readily reacts chemically with hydroxyl and amino groups because of the highly reactive chlorine atom on its ring. This property of triazine makes it suitable as a carrier for polymer synthesis. , Li et al successfully synthesized polyamides containing a triazine structure and exhibited good inhibition of fungal spores . Therefore, it is promising that antimicrobial PET can be prepared by using menthoxytriazine derivatives as diacid units.…”
Section: Introductionmentioning
confidence: 99%